A Highly Warped Heptagon‐Containing sp2 Carbon Scaffold via Vinylnaphthyl π‐Extension. Issue 46 (30th September 2019) - Farrell, Jeffrey M.; Grande, Vincenzo; Schmidt, David; Würthner, Frank
Abstract: A new strategy is demonstrated for the synthesis of warped, negatively curved, all‐sp 2 ‐carbon π‐scaffolds. Multifold C−C coupling reactions are used to transform a polyaromatic borinic acid into a saddle‐shaped polyaromatic hydrocarbon (2 ) bearing two heptagonal rings. Notably, this Schwarzite substructure is synthesized in only two steps from an unfunctionalized alkene. A highly warped structure of 2 was revealed by X‐ray crystallographic studies and pronounced flexibility of this π‐scaffold was ascertained by experimental and computational studies. Compound 2 exhibits excellent solubility, visible range absorption and fluorescence, and readily undergoes two reversible one‐electron oxidations at mild potentials. Abstract : Carbonaceous and curvaceous : A new strategy is described for the synthesis of heptagon‐containing all‐sp 2 ‐hybridized carbon scaffolds from unfunctionalized alkene precursors. This direct approach is applied for the synthesis of a flexible, negatively curved polyaromatic hydrocarbon that exhibits excellent solubility, visible range absorption and fluorescence, and two reversible one‐electron oxidations at mild potentials.